Critical soil organic carbon range for optimal crop response to mineral fertiliser nitrogen on a ferralsol - Musinguzi, P.; Ebanyat, Peter; Tenywa, J.S.; Basamba, T.A.A.; Tenywa, M.M.; Mubiru, D.N. (Cambridge University Press, 2016)
Soil Organic Carbon (SOC) is a major indicator of soil fertility in the tropics and underlies variability in crop response to mineral fertilizers. Critical SOC concentrations that interact positively with N fertilizer for optimal crop yield are less understood. A study was conducted on a Ferralsol in sub-humid Uganda to explore the critical range of SOC concentrations and associated fractions for optimal maize (Zea mays L.) yield response to applied mineral N fertiliser. Maize grain yield response to N rates applied at 0, 25, 50 and 100 kg N ha−1 in 30 fields of low fertility (SOC < 1.2%), medium fertility (SOC = 1.2–1.7%) and high fertility (SOC > 1.7%) was assessed. Soil was physically fractionated into sand-sized (63–2000 µm), silt-sized (2–63 µm) and clay-sized (<2 µm) particles and SOC content determined. Low fertility fields (<1.2% SOC) resulted in the lowest response to N application. Fields with >1.2% SOC registered the highest agronomic efficiency (AE) and grain yield. Non-linear regression models predicted critical SOC for optimal yields to be 2.204% at the 50 kg N ha−1 rate. Overall, models predicted 1.9–2.2% SOC as the critical concentration range for high yields. The critical range of SOC concentrations corresponded to 3.5–5.0 g kg−1 sand-sized C and 9–11 g kg−1 for clay-sized C.